The Vision of Energy Security by Key Power Centers (Russia, China, USA, and the EU) - Yu V. Borovsky (Сравнительная политика)
The 2020s have witnessed increasing instability in energy security. The COVID-19 pandemic, which profoundly impacted the global economy and energy industry; the fierce confrontation between Russia and the West over the war in Ukraine, which has significantly disrupted global energy supplies; the ongoing tensions of tensions in the hydrocarbon-rich Middle East; and imbalances arising from the fourth energy transition are among the key factors destabilizing the global energy supply system, resulting in high volatility in energy prices. Countries’ approaches to energy security remain largely conventional, focusing on three core aspects: security of energy supply, energy independence, and security of energy demand.This study comprehensively analyzes the current understanding of energy security by Russia, China, the USA, the EU, based on their fundamental doctrinal documents. The findings indicate that Russia, as a self-sufficient country and major energy exporter, views its energy security through the lenses of security of energy demand, security of energy supply, and energy independence. China prioritizes security of energy supply and strives for energy independence amid the energy transition, a natural approach given its critical dependence on hydrocarbon imports and status as the world’s largest source of greenhouse gases. The United States, despite becoming a net oil and gas exporter, continues to prioritize security of energy supply and energy independence, with an increasing emphasis on security of energy demand. The European Union, critically dependent on hydrocarbon imports, focuses primarily on security of energy supply and energy independence within the context of the energy transition.While Russia, China, the US, and the EU predominantly view energy security defensively, the US and the EU also adopt an offensive stance. Unlike China, the US, the EU, and Russia politicize their understanding of energy security. Despite this, Russia and China demonstrate openness to international energy cooperation, whereas the US and the EU are more inclined to promote their energy sector interests through confrontation.